Regulating Resilient Supply Chains: An Adaptive Governance Approach to Corporate Responsibility in Sustainable Coastal Economies - Aji Baskoro (Westscience Press, 2026)
This paper examines the legal framework governing climate-resilient supply chains in coastal economies through an adaptive governance lens, with particular reference to Indonesia. As climate change intensifies systemic risks in coastal social-ecological systems, supply chains in fisheries and aquaculture sectors face growing regulatory and institutional challenges. This study addresses two central questions: first, how national and local legal frameworks integrate adaptive governance principles in regulating coastal supply chains; and second, how corporate governance norms respond to climate risks and whether existing legal instruments adequately promote sustainability and resilience. Employing a normative juridical methodology, this research relies on doctrinal analysis of primary and secondary legal materials, including environmental law, maritime and fisheries regulation, regional governance instruments, and corporate law frameworks. Through systematic statutory interpretation and regulatory coherence assessment, the study evaluates the extent to which Indonesian law embodies principles of flexibility, multi-level coordination, risk internalization, and sustainability integration. The findings indicate that while sustainability is normatively embedded in various legal instruments, the regulatory architecture remains fragmented and predominantly compliance-oriented. Corporate governance provisions, although increasingly incorporating environmental responsibility, do not yet fully operationalize climate risk integration within supply chain management. The paper argues that a transition toward adaptive governance requires harmonizing environmental regulation with climate-responsive corporate governance to ensure resilient and sustainable coastal economies.